Great escape at Dunkirk [videorecording (DVD)] - Meyers, Eric, 1959- (PBS, 2018)
Join archaeologists and divers recovering remains of ships and planes lost during World War II's epic Dunkirk operation. Discover new evidence of the ingenious technology that helped save Allied forces from defeat by the encircling Germans.